Dusty Blue Supergiants: News from High-Angular Resolution Observations - W. J. de Wit; R. D. Oudmaijer; J. S. Vink (Advances in Astronomy)
An overview is presented of the recent advances in understanding the B[e] phenomenon among blue supergiant stars in light of high-angular resolution observations and with an emphasis on the results obtained by means of long baseline optical stellar interferometry. The focus of the review is on the circumstellar material and evolutionary phase of B[e] supergiants, but recent results on dust production in regular blue supergiants are also highlighted.